The role and functions of the specialized site on the methodical support of library activities - T. V. Majstrovich (Библиосфера, 2013)
The theoretical and methodological foundation for developing a problem-oriented site on methodological support of library activities are presented. Its structure, purpose of sections and forms of materials provision are considered on the example of the site of the Russian Association of the electronic libraries. Proposed is a site model based on the multimedia platform.